Turkey in the implementation of China’s economic strategy in the Middle East - M. A. Dyakonova (Вестник университета)
The subject of this study is the process of implementation of economic strategy of the People’s Republic of China (hereinafter referred to as PRC, China), especially towards Turkey. The purpose of the article is to determine the current state and prospects of Sino-Turkish cooperation. The methodology of the study is based on an integrated approach with consideration to historical, geographical, economic, and political factors of the regional development of the Middle East and North Africa. China is implementing a new strategy for its foreign policy based on economic cooperation and is focusing on the Middle East and North Africa region. The PRC’s economic interests on this territory are primarily hydrocarbon raw materials and transport infrastructure. Turkey occupies a strategic geographical position in the region and has considerable authority in regional international politics. For more than 50 years, diplomatic relations between China and Turkey have been established and steadily developed. The conclusions drawn from the study are of interest for the implementation of the Russian Federation’s (hereinafter referred to as RF, Russia) foreign policy in the southern direction. Use of the Black Sea basin, active policy of Turkey with regard to the countries of the former Soviet Union (Azerbaijan, Georgia, Kazakhstan, and Armenia) and to the Syrian conflict, actions of Israel towards neighbouring states – all this is important to advance Russia’s interests in this direction. The energy cooperation between the RF and Turkey in the nuclear sphere as regards the supply of natural gas to Europe is also of great importance for the implementation of the state foreign policy.